Calcium-modified granular attapulgite removed phosphorus from synthetic wastewater containing low-strength phosphorus. (June 2022) - Lv, Na; Li, Xiufen; Qi, Xiguang; Ren, Yueping
Abstract: Traditional biological processes combined with chemical precipitation methods can effectively reduce phosphate concentration in wastewater. However, discharge standards required additional advanced treatment technologies, and the removal of low phosphorus concentration is complicated and expensive. This study proposes application of a simple and recyclable adsorbent to remove low-concentration phosphorus from water. The removal efficiency of phosphorus from low-strength synthetic wastewater was investigated and the adsorption mechanism was analyzed. When the initial phosphorus concentration was 2.0 mg/L, the phosphorus adsorption capacity of Ca-GAT increased to 0.891 mg/g from 0.074 mg/g for GAT at 298 K and pH of 7. Phosphorus adsorption on Ca-GAT performs well when the solution pH is in the range of 5–10, and it is not conducive to the adsorption reaction when the solution pH exceeds 11. The competing anions (such as NO3 −, SO4 2−, HCO3 − and F − ) existed, Ca-GAT still performed better in removing phosphorus. Then, the saturated absorbents could be effectively regenerated with a 0.5 mos/L NaOH solution, while desorption efficiency was reduced from 97.11% to 33.06% after fifth regeneration cycle. Finally, Scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS), Fourier-transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS) analysis demonstrated that the Ca 2+ content on the Ca-GAT surface played an important role in capturing phosphate ions from wastewater. Phosphorus was mainly removed via the formation of Ca-phosphorus precipitation. To some extent, ligand exchanges of CO3 2− and OH- with HPO4 2− and H2 PO4 − were also beneficial for phosphorus removal. The present work shows that attapulgite has sustainable and beneficial potential in the removal of low-strength phosphorous in wastewater, and the phosphorus loaded adsorbent can be used in the agriculture as slow-release fertilizer. Graphical abstract: Image 1 Highlights: Ca-GAT was prepared and exhibited a high phosphorus removal efficiency. Its maximum phosphorus adsorption capacity was twelve times that of GAT. Ligand exchange and precipitation were the main mechanisms of phosphorus removal. Ca-GAT has the potential to be used for phosphorus removal from low-strength wastewater.